THE IMPORTANCE OF PRACTICAL TRAINING IN TEACHING THE SUBJECT OF ELECTRICITY AND MAGNETISM - Nabiyeva Firuza Odilovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article discusses the significant role of problem-solving in the study of physics. It presents the most important general methods and approaches to solving problems that help teachers develop students’ physical thinking, provide them with relevant practical knowledge and skills, and use instructional time efficiently. Several problems related to the topic “Electric Charges. Coulomb’s Law. Electric Field Intensity” within the Electromagnetism section are classified into different categories, and their solutions are provided.